2018
DOI: 10.14569/ijacsa.2018.090454
|View full text |Cite
|
Sign up to set email alerts
|

Performance Evaluation of IPv4/IPv6 Transition Mechanisms for Real-Time Applications using OPNET Modeler

Abstract: The problem of the potential depletion of IPv4 addresses has given rise to the development of a new version of the Internet Protocol named IPv6. This version of the protocol offers many improvements, including an increase in the address space from 2 32 to 2 128 and improvements in security, mobility, and quality of service. However, the transition from the current version to the new version (IPv4 to IPv6) is complicated and cannot be performed in a short time. The size and complexity of Internet make this migr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 14 publications
0
10
0
1
Order By: Relevance
“…• Jitter -is defined as the end-to-end transmission delay difference between selected packets in the same packets stream. Unit is ms and lower jitter means better performance [19],…”
Section: Performance Measurement Methodologymentioning
confidence: 99%
“…• Jitter -is defined as the end-to-end transmission delay difference between selected packets in the same packets stream. Unit is ms and lower jitter means better performance [19],…”
Section: Performance Measurement Methodologymentioning
confidence: 99%
“…Thus, instead of keeping different state information for each metric value on the routers, a limited number of state information is kept, and operation delay is minimized. The algorithm of the proposed prioritization model is simulated using the OPNET program [33]. The block diagram of the prioritization algorithm is given in Figure 2 and the flow diagram of the algorithm is presented in Figure 3.…”
Section: Proposed Model and Methodsmentioning
confidence: 99%
“…The manual tunneling had higher, and IPv4 had the lowest end-to-end delay, video conferencing packet delay variation, voice packet end-to-end delay, voice packet loss ratio, video conferencing packet loss rate. It was also found that the manual had the lowest voice MOS and jitter [13]. In the same year, M. S. Ali and T. A. Yahiya configured the 6to4 tunnel, native IPv4, and IPv6 on a network for applications HTTP, remote login, and WLAN.…”
Section: Literature Reviewmentioning
confidence: 98%